Assessment of Cost Management Functions of Quantity Surveyors with Lean Methodology - Anifowose, Maroof Opeyemi; Ola-awo, Wasiu Adeniran; Mohammed, Tanimu U (International Journal of Sustainable Construction Engineering and Technology, 2013)
The Construction industry in Nigeria is made up of a wide variety of activities which include the provision of professional and technical services to clients in the built environment. Despite the provision of these services to a large number of clients worldwide, the construction industry is still awash by the chronic problems of low productivity, insufficient quality, time over-runs, and poor safety, which hinder customer delivered value. The Just-In-Time phenomenon is a characteristic of lean production systems which operate with very little “fat” (e.g. excess inventory extra workers, wasted space).This study aimed at assessing the construction management function of the quantity surveyor in line with the principle of lean methodology (Just-In-Time). This was achieved by exploring the cost management function of the quantity surveyor, to investigate the current practice of cost management by quantity surveying firms. Data for the study were sourced primarily with the use of questionnaire and the subsequent data analysis, which employed the use of descriptive analysis of presenting the data as obtained on tables during the field survey and attempts a rudimentary establishment of patterns using percentages. The study concluded amongst others, that: all activities involved in the cost management function of the quantity surveyor are important, and value adding, corresponding to conversion activities in line with the Just-In-time/lean methodology